Performance and dynamic behaviour of FRP strengthened CFST members subjected to lateral impact. (15th September 2017) - Alam, Md Iftekharul; Fawzia, Sabrina; Zhao, Xiao-Ling; Remennikov, Alex M.; Bambach, M.R.; Elchalakani, M.
Highlights: Experimental lateral impact tests of bare and FRP strengthened CFST members are conducted. The failure modes and dynamic structural responses are investigated to evaluate the effectiveness of FRP wrapping. Externally bonded FRP sheets improved impact resistance by minimising lateral displacement and core concrete cracks' width. Abstract: Due to the increasing popularity of concrete-filled steel tubular (CFST) members, there will be more chances of vehicles/vessels or terrorist attacks on these structures in near future. Fibre-reinforced polymer (FRP) strengthening can be an effective option to reduce impact damage or failure of CFST members. However, existing knowledge is very limited in understanding the behaviour of FRP strengthened CFST structures under lateral impact loading. This paper outlines drop hammer impact test results of a series of experimental programs of bare and FRP strengthened CFST specimens. A total of sixteen CFST specimens were prepared and tested under lateral impact at their mid-span. The results indicate that permanent lateral displacement of CFST members can be reduced up to 18.2% by externally bonded FRP sheets. The effects of FRP type, FRP wrapping direction, carbon fibre-reinforced polymer (CFRP) wrapping layers, wrapping length, and impact velocity were investigated to understand the influences of these parameters on the behaviour of strengthened CFST specimens. CFRP laminates were found to be weak under impact loading when wrapped in only longitudinal direction. However, a combination of longitudinal and hoop layers of CFRP laminates, or only GFRP wrapping, can remarkably minimise the severity of damage and failure of FRP in CFST specimens under lateral impact. A comparison of current test results with recent works has been presented to understand the effect of impact energy on the lateral displacement control ability of FRP strengthened CFST members.